A Football Player's Insider View: Inspiring the Achievement Story of the Turkey Amputee Football National Team - Yalın Aygün; Cemal Gündoğdu; Şakir Tüfekçi; Betül Akyol; Burak Canpolat; Mehmet Ilkım (Selcuk University, 2020)
Turkey wins the European Amputee Football Federation (EAFF) championship after beating England 2-1 in the final held at Istanbul. The aim of this research was to explore, conceptualize and explain the success story of Turkey Amputee Football National Team. Thus, the goal was to present a map of success. One football player was interviewed using open-ended questions. The data were analyzed using thematic analysis. Analysis resulted in a synthesis of the various ways Turkey National Amputee Football Team experienced success: (a) Determination and Team Spirit, (b) Self-sacrifice, (c) Challenging to Limitations, Restrictions and Barriers, and (d) Dependent Images and Expectations. The results are consistent with the building blocks (Positive Emotion, Engagement, Relationships, Meaning, and Accomplishment) of flourishing and well-being suggested by PERMA Theory.